TRANSFORMASI MEDIA KOMUNIKASI DIGITAL DALAM PENTOLOGI TEENLIT JINGGA KARYA ESTI KINASIH - Nabilatur Rohmah; Ririe Rengganis; Suyatno (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The transformation of digital communication media has reshaped various aspects of social life, including the communication practices of adolescents as reflected in contemporary literary works. This study aims to describe the representation of digital communication media transformation in Esti Kinasih’s Jingga teenlit pentalogy through three aspects: the evolution of dominant media, the multimodality of digital communication, and media convergence in the lives of adolescent characters. This research employed a qualitative approach with a descriptive design and content analysis method. The primary data source was Esti Kinasih’s Jingga teenlit pentalogy, consisting of Jingga dan Senja (2010), Jingga dalam Elegi (2011), Jingga untuk Matahari (2017), Jingga untuk Sandyakala Part I (2023), and Jingga untuk Sandyakala Part II (2024), while secondary data were obtained from relevant literature. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, which includes data condensation, data display, and conclusion drawing and verification. The findings reveal that the representation of digital communication media transformation in the Jingga pentalogy encompasses: (1) the evolution of dominant communication media from SMS and telephone calls to social media direct messages, WhatsApp, and application-based services; (2) multimodality through the integration of text, emoticons, images, voice notes, and voice calls within a single communication event; and (3) media convergence that integrates multiple communication functions into a single digital device or platform. This study concludes that the Jingga teenlit pentalogy functions not only as a form of entertainment but also as a sociocultural document that records the progressive transformation of communication culture among Indonesia’s digital generation from 2010 to 2024.